Women’s sport and everyday resistance - Isard, Risa F.; Melton, E. Nicole; Macaulay, Charles D. T. (Frontiers in Sports and Active Living, 2023)
This paper presents a conceptual model to understand the relationship between everyday resistance and women’s sport. Everyday resistance refers to when members of an oppressed group engage in mundane actions (i.e., playing sports) to resist dominant power structures and social norms. After reviewing resistance literature, we identify two levels of everyday resistance for women’s sport: women’s sport as everyday resistance and everyday resistance within women’s sport. The former refers to when women participate in sport, thereby challenging social norms that marginalize women in society and exclude them from sport. The latter refers to how women athletes with intersecting marginalized identities resist the norms of who participates in women’s sport and how, given the norms of sport that privilege whiteness, heteronormativity, and higher social classes among others. The model we introduce advances both sport scholarship and everyday resistance literature and can help scholars conceptualize how women create change in sport and in society—as well as how women athletes create change within women’s sport, specifically.